Conceptual design of chemical devices. Issue 1 (4th December 2020) - Ho, Elliot Ngou‐Tin; Fung, Ka Yip; Wibowo, Christianto; Zhang, Xiang; Ng, Ka Ming
Abstract: Chemical devices are chemical products that transform a feed stream into an outlet stream with the desired attributes by performing reaction, fluid flow, heating, cooling, and/or separations. They resemble small chemical plants and can be described by device flowsheets, similar to the process flowsheets of chemical plants. This article proposes a generic design framework for chemical devices. It shares some steps with Douglas' hierarchical design procedure for chemical processes but has its own distinguishing features such as capturing of consumer preferences, formulation of an engineering statement, and the use of unconventional processing techniques in device manufacturing. Two examples, domestic dehumidifier and air purifier, are discussed to illustrate the design framework. A new dehumidifier design was found using this framework.